2(w-3)+7=1-2w

Simple and best practice solution for 2(w-3)+7=1-2w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(w-3)+7=1-2w equation:


Simplifying
2(w + -3) + 7 = 1 + -2w

Reorder the terms:
2(-3 + w) + 7 = 1 + -2w
(-3 * 2 + w * 2) + 7 = 1 + -2w
(-6 + 2w) + 7 = 1 + -2w

Reorder the terms:
-6 + 7 + 2w = 1 + -2w

Combine like terms: -6 + 7 = 1
1 + 2w = 1 + -2w

Add '-1' to each side of the equation.
1 + -1 + 2w = 1 + -1 + -2w

Combine like terms: 1 + -1 = 0
0 + 2w = 1 + -1 + -2w
2w = 1 + -1 + -2w

Combine like terms: 1 + -1 = 0
2w = 0 + -2w
2w = -2w

Solving
2w = -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
2w + 2w = -2w + 2w

Combine like terms: 2w + 2w = 4w
4w = -2w + 2w

Combine like terms: -2w + 2w = 0
4w = 0

Divide each side by '4'.
w = 0

Simplifying
w = 0

See similar equations:

| 4-x=x | | x^5+x^2+x=0 | | 8x+4=5(x+2) | | 9.40dm=hm | | X-2x=3x-20 | | 6(7+2x)-8x-(y+4)=12 | | 7x+8-x+7=3x+24 | | (x-3)2=15 | | -24=t-29 | | 40-13x=1 | | x^2-4x+6y+10=0 | | 8.5(13x-27)=-119 | | 2(1y-4)=-4y+10 | | 2(3x+9)=-36 | | 36z^2+9z+15=0 | | -11=2+y | | 5(u+4)=9u+32 | | 12x^2=4x | | 24+a=-14 | | 6-6x=10-8x | | -8x+95=-425 | | -14+p=7 | | 4=-n-n | | 18=-8+n | | 16+n/8=26 | | 3(2v+14)=-15v | | y^2+11y+62=0 | | 3(3j+15)=-3(11-5j) | | -4(4w+20)-15=-6w+17+18 | | 3=3(2q-7) | | (98x+27)9+5x-1=6(x+23) | | 9(2k+1)=-4+19k |

Equations solver categories